Impact of Teachers' Practices on Students' Reading Comprehension Growth in Guatemala. Issue 155 (March 2017) - Rubio, Fernando; de Véliz, Leslie Rosales; Mosquera, María Cristina Perdomo; López, Ventura Salanic
Abstract: This article discusses an educational intervention, with a strong emphasis on reading development in a bilingual context, in the Western Highlands of Guatemala (WH), a highly disadvantaged region, where the majority of the population is of Mayan origin and primary education is poor. The majority of the students in the Western Highlands speak a Mayan language as their mother tongue, yet they are generally taught in Spanish. We assisted in the development and implementation of a bilingual/intercultural education model including teacher training at the university level and bilingual materials development. Implementation included education for administrators and teacher coaching. For this intervention, aimed at improving reading outcomes, we report data for the first 3 years of implementation, and offer insights for system‐wide interventions in low‐resource areas.